2021
DOI: 10.1016/j.msard.2021.103083
|View full text |Cite
|
Sign up to set email alerts
|

Status of the neuromyelitis optica spectrum disorder in Latin America

Abstract: Background: Neuromyelitis optica spectrum disorders (NMOSD) is an increasing diagnostic and therapeutic challenge in Latin America (LATAM). Despite the heterogeneity of this population, ethnic and socioeconomic commonalities exist, and epidemiologic studies from the region have had a limited geographic and population outreach. Identification of some aspects from the entire region are lacking. Objectives: To determine ethnic, clinical characteristics, and utilization of diagnostic tools and types of therapy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The demographic characteristics and clinical profiles of the patients in this study were similar to those in other ethnicities reported by previous publications: NMOSD is more prevalent in females (20,(23)(24)(25)(26), with AQP4-IgG detected in over half of NMOSD populations (20,23,25,27). NMOSD patients often suffer from frequent relapse and severe neurological disabilities, with paresthesia, limb weakness, and visual impairment being the most common initial symptoms (15,20,23,27,28). In this study, disease onset in elderly patients was associated with a higher annual EDSS increase compared with disease onset in younger patients, which is similar to the findings of several other studies and may be due to the following aspects (24,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The demographic characteristics and clinical profiles of the patients in this study were similar to those in other ethnicities reported by previous publications: NMOSD is more prevalent in females (20,(23)(24)(25)(26), with AQP4-IgG detected in over half of NMOSD populations (20,23,25,27). NMOSD patients often suffer from frequent relapse and severe neurological disabilities, with paresthesia, limb weakness, and visual impairment being the most common initial symptoms (15,20,23,27,28). In this study, disease onset in elderly patients was associated with a higher annual EDSS increase compared with disease onset in younger patients, which is similar to the findings of several other studies and may be due to the following aspects (24,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 87%
“…The demographic characteristics and clinical profiles of the patients in this study were similar to those in other ethnicities reported by previous publications: NMOSD is more prevalent in females (20,(23)(24)(25)(26), with AQP4-IgG detected in over half of NMOSD populations (20,23,25,27). NMOSD patients often suffer from frequent relapse and severe neurological disabilities, with paresthesia, limb weakness, and visual impairment being the most common initial symptoms (15,20,23,27,28).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Even though a great racial and ethnic heterogeneity exists in Latin America, Mestizos, the blended genetics and cultures over the course of five centuries of white Caucasians of European ancestry with Native Americans and black Africans have emerged as the modern predominant Latin American ethnic population. Whereas MS appears to have an increasing prevalence among Latin Americans, NMOSD observations indicate that this disease is also widely identified throughout the continent [ 13 ]. The current paper reports a multinational regional collaborative study on the clinical characterization of NMOSD from the six Central American and three Caribbean countries.…”
Section: Introductionmentioning
confidence: 99%